Turbulence Intensity as an Indicator for Ischemic Stroke in the Carotid Web - Bae, Taewoong; Ko, Jung Ho; Chung, Jaewoo (World neurosurgery, 2021)
Carotid web (CaW) is reported as one of the causes of cryptogenic strokes. However, its pathophysiology is not known, which makes clinicians debate CaW treatment. The current study presents the mechanism of ischemic stroke in CaW and finds a potential indicator for ischemic stroke in CaW. Computational fluid dynamics (CFD) was applied to computer-aided artificial human CaW models to investigate the correlation between stenosis rate and CaW angle. The CFD results were compared with stroke or symptomatic CaW including adequate reported images for anatomic analysis of the stenosis rate and CaW angle. The CFD result of the CaW models shows that the velocity decreases and the turbulence generation of blood flow increases in the area under CaW (AuCaW). In AuCaW, turbulence intensity (TI) is high in the high stenosis rate and small angle conditions. Moreover, TI remained high in the AuCaW throughout the cardiac cycles. The analysis of 67 anatomic figures appeared in 36 articles merged with CFD results, and a CaW scoring system was introduced for clinicians to determine patients with CaW with a high risk of ischemic stroke. This study is believed to be the first to apply TI to CaW. Because most ischemic strokes in CaW occurred at a high stenosis rate and small angle, TI may be used as a potential indicator of ischemic stroke in CaW. Furthermore, TI is easily used in the daily clinical field by applying CaW scores.